Tugas MANAJEMEN PEMBINAAN AKHLAK DALAM PENGUATAN PENDIDIKAN KARAKTER PESERTA DIDIK DI SEKOLAH DASAR (STUDI KASUS DI SDS PLUS 2 ALMUHAJIRIN KABUPATEN PURWAKARTA) - Wawan Kustiawan; Juandi Azi Wijaya; Tita Sumiarsih; R Supyan Sauri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Amid the growing phenomenon of moral decadence and character crisis that is increasingly concerning today, character education has become an urgent need for the younger generation. Schools, as the primary institutions of education, are expented to shape students not only to be academically intelligent but also to prosess noble character and religiosity. This study aims to describe the management of moral development in strengthening character education for students at SDS Plus 2 Almuhajirin. The research employs a qualitative approach with a case study method. Data collection was conducted through in-depth interviews, participatory observation, and documentation studies. The results show that the moral development management at SDS Plus Almuhajirin runs very well through structured management functions. Planning is outlined in the School Annual Work Plan (RKS) and School Annual Work Plan (RKT) with measurable targets. Organizing involves all school members with clear role divisions. Implementation is carried out through flagship programs such as congregational Dhuha and Dzuhur prayers, the 5S program (Smile, Greeting, Salutation, Politeness, Courtesy), Tahsin learning using the Hijroti method, Clean Friday, SEJABAR (Half an Hour of Cleanliness), as well as Character Ambassadors, Little Doctors, and Environmental Ambassadors. Evaluation uses character report cards and an online parent-teacher communication book (PASO). Supporting factors include the principal's commitment, foundation support, and parental participation. Inhibiting factors are the consistency of teacher role modeling and time constraints. The conclusion of this study is that moral development management at SDS Plus 2 Al-Muhairin has been running effectively and can serve as a model for other schools.